Sequential extraction of antioxidants from Citrus aurantium L. flower and kinetic evaluation of their effect on oil microparticle oxidative stability - Abdessamie Kellil; Rajat Suhag; Maria Concetta Tenuta; Sara Bolchini; Vakare Merkyte; Matteo Scampicchio; Ksenia Morozova; Giovanna Ferrentino (Food Chemistry: X)
This study applied supercritical CO2 and ultrasound-assisted ethanol extraction (UAE) to obtain apolar and polar antioxidant fractions from Citrus aurantium flowers. HPLC-HRMS revealed distinct phytochemical profiles, with the polar extract showing higher phenolic content and antioxidant activity. Linseed oil was co-encapsulated with these extracts at varying concentrations (1, 2, and 5 mg/g of oil) using the Particles from Gas Saturated Solution (PGSS) technique, and the oxidative stability was assessed using isothermal calorimetry. Key kinetic parameters, such as induction time (τ), oxidation rates (Rinh, Runi), and antioxidant efficiency (A.E.), were measured. The polar extract demonstrated superior A.E., further confirmed by the DPPH stopped-flow assay. Co-encapsulation of both extracts produced an additive effect, surpassing the synthetic antioxidant BHT (200 μg/g). This study highlights Citrus aurantium flower extracts as natural antioxidants, enhancing the oxidative stability of encapsulated oils, while offering a sustainable method for bioactive compound recovery for food applications.